Psychopathology, physical complaints and health risk behaviors among youths who were victims of childhood maltreatment: a comparison between home and institutional interventions - Pinto, Ricardo (2013)
Based on investigations of child maltreatment by Child Protective Services (CPS), several children who are identified receive some kind of individual or familial intervention. However, the literature has shown conflicting results in regard to the later functioning of the children who are target of different protective measures in different settings, compared to other youths who receive no intervention. We assessed childhood adversity, psychopathology, physical complaints and health risk behaviors among youths who received one of two different protective interventions during childhood (home vs. institutionalization group), and we compared them with youths who receive no intervention (comparison group). In total, 216 youths participated, with ages ranging from 14 to 23 years (M = 17.05 years, SD = 1.8 years; 105 males, 111 females), including 136 youths that were contacted based on their CPS records completed during their childhood, and 80 youths from the community without CPS identification. Results There were no differences between groups in terms of global psychopathology, global index of risk behaviors, and physical complaints. However, additional analyses showed different associations between each type of risk behavior and different interventions applied. Our findings suggest that when the decision is to keep the child at home, families show limitations applying the rules and supervising after CPS intervention. When the decision is to remove the child from home, the results suggest that professionals need to focus on protecting youths from engaging in risky and destructive acts. Families that do not meet the criteria for CPS investigation also need help to protect their children from subsequent risk behaviors.